3D‐Printed Silicone Soft Architectures with Programmed Magneto‐Capillary Reconfiguration. Issue 4 (15th January 2019) - Roh, Sangchul; Okello, Lilian B.; Golbasi, Nuran; Hankwitz, Jameson P.; Liu, Jessica A.‐C.; Tracy, Joseph B.; Velev, Orlin D.
Abstract: Soft intelligent structures that are programmed to reshape and reconfigure under magnetic field can find applications such as in soft robotics and biomedical devices. Here, a new class of smart elastomeric architectures that undergo complex reconfiguration and shape change in applied magnetic fields, while floating on the surface of water, is reported. These magnetoactive soft actuators are fabricated by 3D printing with homocomposite silicone capillary ink. The ultrasoft actuators easily deform by the magnetic force exerted on carbonyl iron particles embedded in the silicone, as well as lateral capillary forces. The tensile and compressive moduli of the actuators are easily determined by their topological design through 3D printing. As a result, their responses can be engineered by the interplay of the intensity of the magnetic field gradient and the programmable moduli. 3D printing allows us to fabricate soft architectures with different actuation modes, such as isotropic/anisotropic contraction and multiple shape changes, as well as functional reconfiguration. Meshes that reconfigure in magnetic fields and respond to external stimuli by reshaping could serve as active tissue scaffolds for cell cultures and soft robots mimicking creatures that live on the surface of water. Abstract : A new class of soft 3D‐printed actuators and meshes with magnetic response is presented. They are made of homocomposite silicone capillary ink containing iron microparticles. The meshes are floating on water and are actuated via a magnetic field mediated by capillarity. Their response and reconfiguration pattern are programmed by the pattern of the filaments.